Kingdom of Lesotho : Agriculture Public Expenditure Review - World Bank Group (World Bank, Washington, DC, 2020)
Over 70 percent of Lesotho’s population live in rural areas and depend directly or indirectly on agriculture for their livelihood, and growth in the sector is crucial for poverty reduction. Despite the importance of growth in agriculture, productivity remains low and value addition activities in the sector are limited. Low investment in agriculture has left the sector vulnerable to adverse weather impacts and poorly equipped to adapt to climate change. Low agricultural output and productivity, poverty, and heavy reliance on food imports are closely intertwined with food and nutrition insecurity in Lesotho, which impose high costs on the country. Recognizing the agriculture sector’s importance for job creation and inclusive economic growth under a new growth path led by the private sector, the Government of Lesotho (GoL) selected agriculture as one of four productive sectors central in its new national strategic development plan (NSDP) II for 2018-19 to 2022-23, currently under development. To strengthen the alignment between objectives and the allocation of public expenditures to the sector, the GoL asked the Bank for support to agriculture public expenditure review (AgPER) as part of a larger GoL effort to strengthen public financial management. The report is structured as follows: chapter one gives introduction: why an agriculture public expenditure review for lesotho? Chapter two provides an overview of the agriculture sector in Lesotho, outlines some of its main challenges, and provides an overview of the main policy documents that guide investment in the sector. Chapter three describes the data and methodology used for the analysis of this AgPER and is particularly intended for technical staff who work with agricultural budgeting and expenditures. Chapter four is the main analytical chapter. It describes the budget cycle for allocation and reporting public expenditures to agriculture (PEA); looks at discrepancies between budgeted and executed amounts; assesses the nature of PEA between 2011 and 2017; discusses how Lesotho’s PEA align with its own policy objectives for the sector as well as with international commitments, especially under comprehensive Africa agriculture development program (CAADP); and seeks to understand if the public support to the sector is of a nature that may crowd out private investment. Chapter five summarizes the findings of the analysis and provides recommendations for how to strengthen effectiveness and quality of public expenditures to the agriculture sector.